2008
DOI: 10.1007/s10928-008-9084-6
|View full text |Cite
|
Sign up to set email alerts
|

A model based assessment of the CYP2B6 and CYP2C19 inductive properties by artemisinin antimalarials: implications for combination regimens

Abstract: The study aim was to assess the inductive properties of artemisinin antimalarials using mephenytoin as a probe for CYP2B6 and CYP2C19 enzymatic activity. The population pharmacokinetics of S-mephenytoin and its metabolites S-nirvanol and S-4'-hydroxymephenytoin, including enzyme turn-over models for induction, were described by nonlinear mixed effects modeling. Rich data (8-16 samples/occasion/subject) were collected from 14 healthy volunteers who received mephenytoin before and during ten days of artemisinin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Auto-induction of CYP2B6 and CYP2C19 was proposed to be the main mechanism causing the decline of plasma ARN concentrations [36-38]. A semi-physiological pharmacokinetic model taking into account the autoinduction phenomenon has been developed for ARN in healthy subjects [39].…”
Section: Discussionmentioning
confidence: 99%
“…Auto-induction of CYP2B6 and CYP2C19 was proposed to be the main mechanism causing the decline of plasma ARN concentrations [36-38]. A semi-physiological pharmacokinetic model taking into account the autoinduction phenomenon has been developed for ARN in healthy subjects [39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the autoinduction observed with QHS drugs may be a result of autoinduction of CYP3A and/or CYP2B6. This has been shown for CYP2B6 in vivo (Simonsson et al, 2003;Elsherbiny et al, 2008). Induction of CYP3A4 and CYP2B6 mRNA expression by QHS has been observed in primary human hepatocytes and in the human intestinal cell line LS174T (Burk et al, 2005), and activation of CYP3A4 by QHS drugs was found in healthy subjects (Asimus et al, 2007).…”
Section: Discussionmentioning
confidence: 66%
“…Artemisinin ü ü CYP2A6 Nicotine, coumarin [165] CYP2B6 Mephenytoin [166,167] CYP2C19 Omeprazole, mephenytoin [167,168] Bosentan ü CYP2C9 S-Warfarin [169] CYP3A4 Cyclosporine, glibenclamide, simvastatin [169] Carbamazepine ü ü CYP1A2 Caffeine [170] CYP2C9 Warfarin [171] CYP2B6 Bupropion [172] CYP3A4 Midazolam, alprazolam [173,174] Dexamethasone ü CYP3A4 Erythromycin [175] Efavirenz ü ü CYP3A4 Midazolam, atorvastatin [176] Indole-3-carbinol ü CYP1A2 Caffeine [177,178] Omeprazole ü CYP1A2 Caffeine [179,180] PAHs* ü CYP1A1 qPCR z [181] CYP1B1 qPCR z [182] Phenobarbital § ü ü CYP1A2 Theophylline [183] CYP2B6 Cyclophosphamide [184] CYP2C19 Hexobarbital [185] CYP3A4 Ethynylestradiol [186] Phenytoin ü ü CYP1A2 Theophylline [187] CYP2B6 Cyclophosphamide [188] CYP3A4 Lopinavir, midazolam [173,189] Rifampicin ü CYP1A2 Tizanidine, caffeine [190] CYP2B6 Bupropion [191] CYP2C8 Repaglinide, pioglitazone, rosiglitazone [192][193][194] CYP2C9 Warfarin, tolbutamide, glipizide [195,196] CYP2C19 Omeprazole [197] CYP3A4 Midazolam, nifedipine, repaglinide, zolpidem [6,[198][199][200] Ritonavir (with lopinavir) ü CYP1A2 Caffeine [201] CYP2B6 Buprop...…”
Section: Pxr Car Ahrmentioning
confidence: 99%